Dr. Antonio Fernández Mirabal: exemplary professor, maxillofacial surgeon and oncologist - Raul Jorge Pupo Triguero; Israel Manuel Fagundo Pino (Editorial Ciencias Médicas, 2014)
Dr. Antonio Fernández Mirabal joined the School of Dentistry of Havana as Oral Surgery Instructor in February 1962. One month later he was sent to the National Institute of Oncology and Radiobiology for a course on Oral Oncology. Upon completion of the course, he started an ascending career at both the School and the Institute characterized by outstanding professional, academic and scientific achievements. The objective of this work is to provide information about the professional, academic and research career of Dr. Antonio Fernández Mirabal. in May 2013 an interview was conducted with Dr. Fernández Mirabal. His teaching file was then consulted at the Human Resources Department of the School of Dentistry of Havana. Other bibliographic sources were also consulted. Iinformation was found about his school training, family environment, undergraduate and graduate university training, research topics, his contribution to undergraduate and graduate teaching, as well as the titles obtained, and medals and awards received during more than 50 years of professional life. The life and work of this outstanding professor is an example to be followed by young medical graduates in general, and particularly by maxillofacial surgeons, oncologists, and head and neck surgeons. Key words: biographical data, maxillofacial surgery, emeritus professor.